Глава 3.16. Особливості розгляду спорів, що виникають із земельних відносин та примусове виконання рішень у даних категоріях справ - Дудаш, Мирослава Георгіївна (Цивільний та виконавчий процес: міжгалузеві зв’язки. Особливості розгляду судами певних категорій справ та виконання судових рішень. Монографія, 2024)
The chapter is devoted to the peculiarities and problematic aspectsof consideration of certain categories of disputes arising from land relations by courts of civil, economic and administrative jurisdiction, as well as to the problems of enforcement of decisions in these categories of cases. In particular, considerable attention is paid to the practical problems of jurisdiction in certain categories of land disputes, especially in disputes in which one of the parties is a state authority or a local self-government body; the guiding explanations of the Supreme Court and higher specialized courts, as well as current judicial practice on this occasion, are analyzed. In addition, the problematic aspects of court consideration of cases of alienation of land for public needs were investigated, the imperfection of the relevant legal regulation was noted. Peculiarities of enforcement of court decisions in disputes arising from land relations were studied, in particular, a significant predominance of state executors over private executors was noted. The problems of the implementation of court decisions, in which the collegial body of local self-government is the obligated party, and the implementation of which depends on the adoption of a decision by such a body within its exclusive powers, were analyzed in detail, and the actual impossibility of enforcing such decisions was ascertained. A conclusion was reached about the need for further improvement of both material and procedural legislation in the field of consideration of disputes arising from land relations and enforcement of decisions in this category of cases.